Comparative analysis of Dark Triad traits in relation to performance and self-reported emotional intelligence - Denogent, Louana Marie; Megías-Robles, Alberto; Fernández-Berrocal, Pablo; Gómez-Leal, Raquel (Elsevier, 2025)
Interest in the Dark Triad (DT) traits - Machiavellianism, narcissism, and psychopathy - and their association with maladaptive behaviors has surged in recent years. Research has focused on identifying protective factors such as Emotional Intelligence (EI), but the literature has yielded mixed results regarding this relationship. Our study seeks to explore this relationship from two distinct perspectives of EI: self-report and performance-based measures. To achieve this aim, 222 participants (Mage = 22.01, SD = 4.54, ages 19–60) completed the Trait Meta Mood Scale (TMMS), a self-report measure, and the Mayer Salovey Caruso Emotional Intelligence Test (MSCEIT), a performance-based assessment, to evaluate EI, and the Short Dark Triad (SD-3) was used to evaluate DT traits. Our findings revealed a significant negative correlation between the traits of psychopathy and narcissism and EI scores when using the MSCEIT. However, when utilizing the TMMS, we only identified a positive and significant association between narcissism and EI. These findings underscore the importance of considering the type of EI measurement when examining this relationship. Moreover, we identified sex differences in the study variables and found that sex plays a moderating role in the studied relationship. We discuss the limitations and clinical implications of these findings.
Keywords: Narcisismo; Personalidad - Trastornos; Inteligencia emocional; Maquiavelismo; Identidad (Psicología); Dark triad (DT); Machiavellianism; Narcissism; Psychopathy; Emotional intelligence (EI)